2002
DOI: 10.3310/hta6160
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of bupropion and nicotine replacement therapy for smoking cessation: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 342 publications
6
109
1
6
Order By: Relevance
“…[57][58][59][60] Although several studies have reported adherence to SSRIs for the treatment of depression, 61,62 none have evaluated adherence to bupropion SR, and a recent meta-analysis of the smoking cessation pharmacotherapy literature did not address the issue. 63 A better understanding of the predictors, including genotype, of nonadherence to bupropion therapy is needed. The fact that, in the present study, female carriers of the A1 allele were more likely to stop taking bupropion due to side effects suggests that efforts to better understand the biological contributors to nonadherence should begin with these individuals.…”
Section: Ge Swan Et Almentioning
confidence: 99%
“…[57][58][59][60] Although several studies have reported adherence to SSRIs for the treatment of depression, 61,62 none have evaluated adherence to bupropion SR, and a recent meta-analysis of the smoking cessation pharmacotherapy literature did not address the issue. 63 A better understanding of the predictors, including genotype, of nonadherence to bupropion therapy is needed. The fact that, in the present study, female carriers of the A1 allele were more likely to stop taking bupropion due to side effects suggests that efforts to better understand the biological contributors to nonadherence should begin with these individuals.…”
Section: Ge Swan Et Almentioning
confidence: 99%
“…Using data from two randomized pharmacogenetic trials of tobacco dependence treatment, we have estimated the potential effect on treatment costs and long-term survival of using genetic testing to choose between TN and bupropion for individual smokers. Our approach differs from the previous cost-effectiveness analyses of tobacco dependence treatment [30][31][32][33][34][35][36] in the following ways: (i) we consider Under all parameter combinations that we considered, non-tailored varenicline was the most effective (and expensive) admissible treatment. Bupropion was dominated only in the best-case scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although others have investigated the cost-effectiveness of pharmacologic smoking-cessation interventions, [30][31][32][33][34][35][36][37] we are the first to include a pharmacogenetic tailoring arm in such an evaluation. These previous studies have suggested that pharmacotherapy is cost-effective compared to no treatment or counseling alone, with ICERs in the range of $800-$1200 per quitter and $900-$11 200 per LY, depending on the regimen and the age and sex of the smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reviews Woolacott et al, 2002) (2002), we considered two scenarios for the control 12-month cessation probability, p CON . We assumed a 1% spontaneous annual quit rate, plus an additional 5.1% using brief advice (3-10 min) as the comparator or an additional 11.2% using more intensive individual counseling (>10 min) as the comparator (Nielsen & Fiore, 2000).…”
Section: Effectiveness Model and Data Sourcesmentioning
confidence: 99%